The influence of thermal treatment of the porous glass plates on the character of their scattering in visible spectral region - Antropova, Tatyana V.; Anfimova, Irina N. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The pore structure and light transmission of the high-silica porous glasses in visible spectral region are investigated depending on a temperature of their thermal treatment and composition of the initial two-phase alkali borosilicate glasses. The character of light transmission in porous glasses is analyzed considering the features of their pore space structure and processes occurring in porous glass upon heating. It is shown that with an increase in temperature of thermal treatment of the porous glasses of different composition the pore size increases, and their specific surface decreases (at practically constant common porosity), which is due to the processes of pore overcondensation, that occur owing to the regrouping and change of packing density of the secondary silica particles. It is shown that introducting phosphate and fluoride ions in the basic alkali borosilicate glass results in an increase in the light attenuation factors of the porous glasses owing to an increase in the sizes of liquation areas of heterogeneity in initial two-phase glasses, formation of larger pores and presence of the nanostructured microcrystalline phases in the porous glasses.
Optica Applicata, Vol. 40, 2010, nr 2, s. 285-291
Keywords: optyka; phase-separated alkali borosilicate glasses; porous glass; light transmission